A survey of surgical team members' awareness and perceptions toward the implementation of the surgical safety checklist in gynecological and obstetrical operations. Issue 30 (30th July 2021) - Gong, Junming; Sheng, Bo; Bian, Ce; Yang, Lingyun
Abstract : Abstract: The World Health Organization Surgical Safety Checklist was developed to improve communication in perioperative care, reduce mortality and complications of patients, and ensure the consistent use of procedures for safe surgery. Despite the increased awareness of the checklist, the implementation compliance is reported as low and the degree of completeness varies. This study aimed to explore the possible supportive factors for the effective implementation and to identify potential awareness and barriers to its implementation in gynecological and obstetrical operation. A survey using a cross-sectional design that included surgeons, anesthetists, and operating room nurses was performed. We used an online link to distribute the survey to all eligible surgical team members in our hospital. The survey contained various aspects of perceptions on the Surgical Safety Checklist and an open-ended question that allowed respondents to offer their opinions on the topic. The overall self-reported awareness of the checklist within each professional group was high. The awareness of surgeons was lower than that of operating room nurses, particularly in the Time-out section. Most participants believed that operating room nurses ranked the highest compliance to the protocols, while surgeons stayed the lowest. Active leadership with experienced operating room nurses, good training for surgical team members, and simplification of the checklist would be the positive factors for the effective implementation. Although there is a high acceptance and adequate self-reported awareness of the Surgical Safety Checklist, it is not always possible to implement it successfully. Our findings suggest that with experienced and effective leadership, barriers to implementation can be overcome. With positive perception and commitment, the Surgical Safety Checklist is easy to implement and it can make a profound improvement on the safety of surgical care. Moreover, a strategy of repetitive training and assessment on the part of the involved health care professionals may be necessary to further improve patients' safety during surgery.